Implementation of Media Inovation for Improving Oral Health Maintenance Behavior In Preschool Students In Tanjung Village, Pakis Aji District, Jepara Regency - Kholifah Nur Ijazati (Wealth Community Empowerment, 2024)
Preschool-age children are one of the vulnerable groups to oral health issues. At this age, dental caries is a common oral health problem encountered. This is because the enamel structure of primary teeth in children is thinner compared to permanent teeth. Additionally, excessive consumption of cariogenic foods without balanced toothbrushing skills contributes to the faster occurrence of dental caries. To reduce the risk of severe dental caries, efforts are needed to improve oral health maintenance behaviors through oral health education programs. The success of oral health education can be influenced by the use of instructional media. Creative and innovative instructional media can enhance student motivation to learn. The aim of community service is to enhance the knowledge and skills of TK Putra Bangsa students in oral health maintenance. The program implementation involves stages of preparation, execution, and evaluation. The target participants include students, parents, and teachers of TK Putra Bangsa a in Tanjung Village, Pakis Aji District, Jepara Regency, Central Java. This activity took place from October 23 to 27, 2023. Data collection instruments include examination forms, hygiene index forms, and interview forms for parents and teachers. The results of this activity show an improvement in the knowledge of students, parents, and teachers regarding oral health maintenance efforts, along with the implementation of the daily school toothbrushing program.